Sanitizing agents for virus inactivation and disinfection. Issue 2 (24th May 2020) - Lin, Qianyu; Lim, Jason Y. C.; Xue, Kun; Yew, Pek Yin Michelle; Owh, Cally; Chee, Pei Lin; Loh, Xian Jun
Abstract: Viral epidemics develop from the emergence of new variants of infectious viruses. The lack of effective antiviral treatments for the new viral infections coupled with rapid community spread of the infection often result in major human and financial loss. Viral transmissions can occur via close human‐to‐human contact or via contacting a contaminated surface. Thus, careful disinfection or sanitization is essential to curtail viral spread. A myriad of disinfectants/sanitizing agents/biocidal agents are available that can inactivate viruses, but their effectiveness is dependent upon many factors such as concentration of agent, reaction time, temperature, and organic load. In this work, we review common commercially available disinfectants agents available on the market and evaluate their effectiveness under various application conditions. In addition, this work also seeks to debunk common myths about viral inactivation and highlight new exciting advances in the development of potential sanitizing agents. Abstract : Virus pandemics are recurrent in human history, and one of the major means of human‐to‐human viral transmissions occur through contact with contaminated surfaces. Herein, the authors provide a summary of the major commercially available sanitizing agents used to inactivate viruses and critically evaluate their effectiveness to do so.